Synthesis, Characterization, Crystallographic Studies of 5-Acetyl-8-hydroxyquinoline and Their Chalcone Derivatives - Vagish, C.B.; Kumara, Karthik; Lokanath, N.K.; Kumar, K. Ajay; Chandrasherkar, P.G. (Asian Journal of Chemistry, 2020)
An efficient, easy and one pot synthesis for the Friedel-Craft acetylation reaction of quinolines was developed. The reaction between 8-hydroxyquinoline and acetyl/benzoyl chloride in nitrobenzene immediately flocculates as yellow precipitate. On further addition of Lewis acid causes the Friedel-Craft acetylation leads to formation of acetylated quionlines in good yields. The structure of compound 5-acetyl-8-hydroxyquinoline (3) was confirmed by single crystal X-ray diffraction studies. The compound crystallizes in the monoclinic crystal system with the space group P21/c. The synthesized acetylated quionlines undergoes condensation reaction with aromatic aldehydes leads to 8-hydroxyquinoline chalcones derivatives. The products were characterized by spectral studies, elemental analysis and single crystal X-ray diffraction studies.